Geographic areas susceptible to Fusarium oxysporum in strawberry crop in Guanajuato, México (Bioagro, 2020)
Fusarium oxysporum is the most frequent fungus in the complex of species that make up the disease known as strawberry drying. The objective of this work was to determine the environmental suitability that favors the incidence of this fungus. A total of 174 strawberry production units were sampled to determine the presence of F. oxysporum by morphological characterization. Into positive cases, environmental suitability was evaluated through the maximum entropy algorithm (MaxEnt) with 22 bioclimatic variables as predictors. It was found that in the State of Guanajuato, Mexico, a total surface of 174,580 ha, had climatic conditions to promote the incidence of F. oxysporum. The climatic variables that mainly promote this incidence were the warmest four-month period (31%), the humidity regime (26 %) and the altitude of the zone (18 %).
Keywords: MaxEnt; Environmental suitability; strawberry dryer